INTERAKSI SOSIAL ANTARA KELOMPOK MASYARAKAT ISLAM DAN KRISTEN DI KOTA TERNATE - Arifuddin Ismail (Al-Qalam, 2009)
This article is a summary of the research on religious group social distancemeasurement in Ternate. Data accumulated from questionnairesto 100 respondents and analyzed descriptively.Result shows that, in general, social interaction as friendship, job, socialpolitics, social religious and kinship relation of ethnic and religiousgroups is significantly close and categorized good.The friendship relation is the item with the highest percentage(67.5%) showing that the respondents did not consider religiousidentity as the relationship blockage. It is while the kinship relationwas at the lowest percentage 40% showing that most of respondentsdid not want " other people" to be a member of theirfamily